2009
DOI: 10.1590/s0066-782x2009001200014
|View full text |Cite
|
Sign up to set email alerts
|

Doenças cardiovasculares antes e após o programa saúde da família, Londrina, Paraná

Abstract: Background: The reduction in morbidity and mortality rates from diseases of the circulatory system (DCS) is one of the greatest challenges in primary care, and the implementation of the Family Health Program provides access to the multisectoral and integrated measures required for dealing with these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…A study between 1998 and 2007 on cardiovascular diseases in Londrina/PR state showed higher admission coefficients for men, for three cause groups: IHD, CVD, and heart failure for most age ranges. CVD-related hospital admission was also found to have significantly increased among men, unlike the findings in this study, which showed that most hospital admissions due to DM, CVD, and IHD regarded female patients ( 11 ) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A study between 1998 and 2007 on cardiovascular diseases in Londrina/PR state showed higher admission coefficients for men, for three cause groups: IHD, CVD, and heart failure for most age ranges. CVD-related hospital admission was also found to have significantly increased among men, unlike the findings in this study, which showed that most hospital admissions due to DM, CVD, and IHD regarded female patients ( 11 ) .…”
Section: Discussioncontrasting
confidence: 99%
“…This study results showed that CVDs are found to have higher hospital lethality indices (10%), as compared to the remaining evaluated diseases. A study that was conducted in Niterói confirms those findings, as it showed increased hospital mortality coefficients due to CVDs ( 11 ) .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation